2020
DOI: 10.1111/ijfs.14774
|View full text |Cite
|
Sign up to set email alerts
|

Influences of freeze‐ and spray‐drying vs. encapsulation with soy and whey proteins on gastrointestinal stability and antioxidant activity of Mediterranean aromatic herbs

Abstract: Chemical and biological characterization of selected Mediterranean aromatic herbs after drying processes vs. encapsulation with two protein carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Spray drying of rosemary extracts without carriers resulted in production yields between 17.1 and 74.96%, in a previous report (Chaul, Conceição, Bara, Paula, & Couto, 2017), in contrast to the 87.1-92.7 recoveries reported here for R-WPI and R-WIN, respectively. Similar solids recovery (75%) was reported when aqueous rosemary extracts were freeze dried and used to prepare extracts that were subsequently spray dried with whey protein isolate (Bilušić et al, 2020). In another study, spray dried proliposomes prepared with freeze dried rosemary extracts were obtained with recoveries of only 20.1-45.8%, substantially lower than our results (Bankole, Osungunna, Souza, Salvador, & Oliveira, 2020).…”
Section: Solids Recovery and Polyphenol Retentionsupporting
confidence: 86%
See 2 more Smart Citations
“…Spray drying of rosemary extracts without carriers resulted in production yields between 17.1 and 74.96%, in a previous report (Chaul, Conceição, Bara, Paula, & Couto, 2017), in contrast to the 87.1-92.7 recoveries reported here for R-WPI and R-WIN, respectively. Similar solids recovery (75%) was reported when aqueous rosemary extracts were freeze dried and used to prepare extracts that were subsequently spray dried with whey protein isolate (Bilušić et al, 2020). In another study, spray dried proliposomes prepared with freeze dried rosemary extracts were obtained with recoveries of only 20.1-45.8%, substantially lower than our results (Bankole, Osungunna, Souza, Salvador, & Oliveira, 2020).…”
Section: Solids Recovery and Polyphenol Retentionsupporting
confidence: 86%
“…In particular, the addition of whey protein had a beneficial effect on the solids recovery in this study, since both groups (R-WPI and R-WIN) presented higher recovery (~90%) when compared to soy protein isolate samples (R-SPI and R-SIN, 60% and 70% respectively). Similar improvement based on drying carriers was observed elsewhere (Bilušić et al, 2020;Tontul, Topuz, Ozkan, & Karacan, 2016). It has been suggested that the efficiency of solids recovery can be modulated by differences in protein content of the carrier (Tontul et al, 2016) but in this study, both protein isolates had similar protein content (80%) and therefore, this factor should not play a significant role on the observed results.…”
Section: Solids Recovery and Polyphenol Retentionsupporting
confidence: 77%
See 1 more Smart Citation
“…The literature has shown that the selection of proper wall materials for encapsulating bioactive compounds in the plant extracts plays an important role in the retention of the desired compounds and the antioxidant activity of the obtained microcapsules (Bilušić et al, 2021; Labuschagne, 2018; Yilmaz et al, 2021). Many studies have stated that maltodextrins are one of the most efficient and cost‐effective wall materials for encapsulating bioactive phytochemicals but the poor emulsifying capacity limited their single application for the encapsulation of hydrophobic and volatile compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to freeze‐drying, spray drying is a convenient, cost‐effective, higher applicable, and scalable encapsulation procedure in the food and pharmaceutical industries (Rezvankhah et al., 2020). Spray drying is an interesting alternative means of increasing the stability of powdered foods and food ingredients (Bilušić et al., 2020; González et al., 2019). Freeze drying has been used to dry the nattokinase (Garg & Thorat, 2014).…”
Section: Introductionmentioning
confidence: 99%